Development of a Training Curriculum for Hospital Security About Autism Spectrum Disorder. Issue 3 (April 2021) - Christiansen, Audrey; Harstad, Elizabeth; Sideridis, Georgios; Weissman, Laura
ABSTRACT: Objective: To evaluate whether a newly developed autism spectrum disorder (ASD)-training curriculum for hospital security officers improves comfort, knowledge, and practice. Methods: Participants were security officers. The ASD-training curriculum was a 45-minute interactive session, adapted from trainings developed for other types of hospital providers. The curriculum included information regarding the presentation of, and challenges faced by, children with ASD in the hospital setting. Officers completed surveys before (T1), immediately after (T2), and 3 months after (T3) the training to assess comfort, knowledge, and practice. Comfort (Likert scale 1–5; 5 = highest) and knowledge (11 yes/no questions) questions were adapted from previous measures. Application of skills was assessed using case scenarios (at T1, T2, and T3) and with officers' report of using various strategies (at T1 and T3; Likert scale 1–5; 5 = always). Data were analyzed using repeated-measures analysis of variance and a series of paired contrast. Results: For the 114 officers who completed surveys, mean comfort scores significantly increased from T1 to T2 (3.48 vs 3.9; p < 0.05), and these gains were maintained at T3 (4.1). Mean percent correct on knowledge questions significantly increased from T1 to T2 (74.6% vs 84.0%; p < 0.05) and was maintained at T3 (82.9%). Officers reported using 2 ASD-supportive strategies significantly more between T1 and T3: using pictures and written communication and asking the caregivers for advice. Conclusion: This newly developed ASD-training curriculum for hospital security officers resulted in an immediate increase of self-reported comfort and demonstrated knowledge with continued gains 3 months after training. Abstract : This article has supplementary material on the web site: www.jdbp.org.